Structural changes in China's flow of funds (1992–2022): A Who-to-Whom model - Nan Zhang; Li Zhu (Quantitative Finance and Economics)
We aimed to compile the flow of funds and stock matrix based on the Who-to-Whom (W-t-W) model. Our objective was to analyze structural changes in China's flow of funds and macroeconomic regulation. To strengthen macroeconomic monitoring, we examined the characteristics of fund sources and uses across sectors from a sectoral perspective of the flow of funds. Utilizing data on fund flows and stocks, we constructed the Chinese flow-of-funds matrix and financial asset-liability matrix for the period 1998–2022. Furthermore, time series methods were introduced to track the flow of funds and conduct influence and sensitivity analysis of assets and liabilities. We also performed a multiplier analysis of the fluctuations in the flow of funds and discuss the position and role of the Financial Corporation and Government sector in the financial market.